Data Envelopment Analysis in the Assessment of the Efficiency of Local Government Units: The Case of LAG “Polcentrum” - Marcin Walczak; Edyta Marcinkiewicz (Problemy Zarządzania, 2022)
Purpose: The main aim of this paper is to examine the performance in terms of efficiency of six Polish municipalities associated in Local Action Group (LAG) “Polcentrum” with the use of Data Envelopment Analysis (DEA) method. Design/methodology/approach: Despite the specific character of their activities, municipalities are subject to the same assessment in terms of effectiveness and efficiency as private for-profit organizations. However, there are some differences between public and private sector entities with this respect. Helpful in such an issue can be DEA, which is a method especially suitable for the assessment of the efficiency of non-profit organizations, including local government units. Findings: Our analysis allows for concluding that the studied municipalities perform in fact quite uniformly in terms of their efficiency. Therefore, such results are in favor of the statement that due to close cooperation the units may become more homogeneous in terms of performance. Research limitations/implications: The employed DEA method does not allow for concluding whether this unification is associated with improvement in all the units. What needs to be strongly emphasized is that DEA calculates the “relative” efficiency, so it can show how well a given unit is doing when compared to other peer units, but not compared to a “theoretical maximum”. Originality/value: What distinguishes this study is that the administrative units under investigation are very closely related in terms of geographic location, but also in terms of extensive cooperation in LAG. On this basis, we pose a research question of whether such a close relationship translates into a similarity in terms of their performance.